Microscopical discrimination of human head hairs sharing a mitochondrial haplogroup. Issue 1 (21st September 2020) - Koch, Sandra L.; Liebowitz, Corey; Shriver, Mark D.; Jablonski, Nina G.
Abstract: In forensic analyses, determining the level of consensus among examiners for hair comparison conclusions and ancestry identifications is important for assessing the scientific validity of microscopical hair examinations. Here, we present data from an interlaboratory study on the accuracy of microscopical hair comparisons among a subset of experienced hair examiners currently analyzing hair in forensic laboratories across the United States. We examined how well microscopical analysis of hair can reliably be used to differentiate hair samples, many of which were macroscopically similar. Using cut hair samples, many sharing similar macroscopic and microscopic features, collected from individuals who share the same mitochondrial haplogroup as an indication of genetic relatedness, we tested multiple aspects that could impact hair comparisons. This research tested the extent to which morphological features related to ancestry and hair length influence conclusions. Microscopical hair examinations yielded accurate assessments of inclusion/exclusion relative to the reference samples among 85% of the pairwise comparisons. We found shorter hairs had reduced levels of accuracy and hairs from populations examiners were not familiar with may have impacted their ability to resolve features. The reliability of ancestry determinations is not yet clear, but we found indications that the existing categories are only somewhat related to current ethnic and genetic variation. Our results provide support for the continued utility of microscopical comparison of hairs within forensic laboratories and to advocate for a combined analytical approach using both microscopical analysis and mtDNA data on all forensic analyses of hair.